MATERNAL AND PERINATAL OUTCOMES IN PRETERM BIRTH DEPENDING ON THE METHOD OF DELIVERY - Баринов, Сергей Владимирович; Искаков, Серик Саятович; Аманбекова, Сауле Батыровна; Ятманов, Алексей Николаевич; Богатырёва, Анна Николаевна (Mother and Baby in Kuzbass, 2023)
The aim of the research – to identify risk factors and assess maternal and perinatal outcomes in preterm birth, depending on the method of delivery.Materials and methods. The retrospective study, which included 281 patients with preterm labor. Group I consisted of 150 patients were delivered by caesarean section. Group II (n = 131) included patients who had vaginal delivery. The patients of each group were divided depending on the term of delivery: in the period of 32-36 weeks 6 days, 28-31 weeks 6 days and 22-27 weeks 6 days. Newborns of the two groups were compared according to the state at the time of birth, the length of stay in the intensive care unit and in the neonatal care unit. When analyzing the course of pregnancy, risk factors for preterm birth were identified, and a comparison was made of the course of the postpartum / postoperative period.Results. Risk factors for preterm birth were identified: moderate preeclampsia – 30 % in the first group and 6.1 % in the second group (p < 0.001), uterine scar after cesarean section 29.3 % in patients of the first group and 6.1 % in patients of the second group (p < 0.001), premature rupture of membranes – 21.3 % and 48.9 %, respectively (p < 0.001).Conclusion. There was a decrease in the length of stay in the intensive care unit and the neonatal care unit in the group of children born through the natural birth canal. The duration of the time from rupture of membranes to delivery, and the method of delivery in the compared groups did not have a significant impact on the condition of newborns, and did not complicate the course of the postoperative/postpartum period in women.Adverse outcomes in newborns were in the group with extremely early preterm birth.The authors declare no possible conflicts of interest. The study was conducted without sponsorship.
Keywords: preterm birth; caesarean section; glucocorticosteroids; time from rupture of membranes to delivery; antibiotics; preeclampsia; premature rupture of membranes